Quality of life in children treated with restrictive diet for inherited metabolic disease. Issue 4 (30th May 2013) - Eminoglu, Tuba F.; Soysal, Sebnem A.; Tumer, Leyla; Okur, Ilyas; Hasanoglu, Alev
Abstract: Background: The aim of this study was to investigate the quality of life (QoL) of a group of patients with inherited metabolic diseases (IMD) who were treated with restrictive diet. Method: A total of 68 patients (35 boys, 51.5%; 33 girls, 48.5%) with IMD (organic acidemia [OA], n = 14; disorder of carbohydrate metabolism [CMD], n = 33; and disorder of amino acid metabolism [AMD], n = 21) and their parents were inteviewed. Both parents completed a QoL Scale for Metabolic Diseases–Parent Form, a KINDL parent questionnaire, and a depression form. All patients aged ≥4 years completed a questionnaire themselves, including the KINDL‐Kid and KINDL‐Kiddo self‐reports. The semi‐standardized interviews were carried out with patients and their parents in a clinical setting. Results: The patients with bad diet compliance had lower scores for school labeling and perception of disease on both the parent and child questionnaire forms ( P < 0.05). The patients were then divided into three groups (OA, CMD, AMD) for further analysis. Differences were seen between groups with regard to scores of physical function and school performance according to QoL Scale for Metabolic Diseases–Parent Form ( P < 0.01). According to parent perceptions, the CMD patients had better QoL with regard to emotional wellbeing. Conclusion: As negative effects of the disease increased, the QoL of IMD patients and their parents decreased in terms of emotional, physical, and cognitive function. Application of expanded newborn scanning programs, early diagnosis, regular follow up, and family education would lessen the effects of the disease and improve the QoL of both families and children.